2017
DOI: 10.1113/jp273558
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diastolic and autonomic dysfunction are aggravated by central chemoreflex activation in heart failure with preserved ejection fraction rats

Abstract: Key pointsr Heart failure with preserved ejection fraction (HFpEF) is associated with disordered breathing patterns, and sympatho-vagal imbalance.r Although it is well accepted that altered peripheral chemoreflex control plays a role in the progression of heart failure with reduced ejection fraction (HFrEF), the pathophysiological mechanisms underlying deterioration of cardiac function in HFpEF are poorly understood.r We found that central chemoreflex is enhanced in HFpEF and neuronal activation is increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
184
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(192 citation statements)
references
References 61 publications
(70 reference statements)
5
184
1
2
Order By: Relevance
“…These comorbidities are frequent in patients with HFpEF or HFmrEF, thus suggesting the presence of chemoreflex dysfunction in these patients. In fact, Toledo and colleagues recently reported that the central chemoreflex is enhanced in HFpEF (Toledo et al, 2017). These authors observed that the activation of the central chemoreflex pathway by hypercapnia exacerbates sympatho-vagal imbalance in HFpEF rats, and that sympathetic blockade with propranolol attenuates the response of cardiac sympathetic modulation.…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…These comorbidities are frequent in patients with HFpEF or HFmrEF, thus suggesting the presence of chemoreflex dysfunction in these patients. In fact, Toledo and colleagues recently reported that the central chemoreflex is enhanced in HFpEF (Toledo et al, 2017). These authors observed that the activation of the central chemoreflex pathway by hypercapnia exacerbates sympatho-vagal imbalance in HFpEF rats, and that sympathetic blockade with propranolol attenuates the response of cardiac sympathetic modulation.…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
“…These authors observed that the activation of the central chemoreflex pathway by hypercapnia exacerbates sympatho-vagal imbalance in HFpEF rats, and that sympathetic blockade with propranolol attenuates the response of cardiac sympathetic modulation. In addition, these authors showed that neuronal activation in the RVLM was increased in HFpEF rats compared with sham rats (Toledo et al, 2017). However, further studies are needed to better understand the mechanistic intricacies of these new findings.…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
“…; Toledo et al . ). V T oscillations were analysed by the calculation of the coefficient of variation of the magnitude of each V T cycle in the same respiratory segments.…”
Section: Methodsmentioning
confidence: 97%
“…The end‐systolic volume (ESV) and EDV were calculated using the Teicholz method ([ESV = 7 × ESD3/(2.4 + ESD)] and [EDV = 7 × EDD3/(2.4 + EDD)], respectively) (Lang, ; Toledo et al . ; Del Rio et al . ; Andrade et al .…”
Section: Methodsmentioning
confidence: 98%
“…The proinflammatory state is attributed to increased central autonomic tone via a central chemoreflex pathway that is responsible for causing diastolic dysfunction and imbalance between the sympathetic and parasympathetic setpoint. 14 Pressure-volume loops show an upward or leftward shift of the LV end-systolic pressure volume relationship, reflecting increased end-systolic myocardial stiffness. Patients with HFpEF typically have normal LV chamber size and greater wall thickness (concentric remodeling), resulting in lower brain natriuretic peptide (BNP) levels.…”
Section: Pathophysiology Of Hfpefmentioning
confidence: 99%